2020
DOI: 10.1021/acsami.0c14119
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Engineering of a MoO2–CeF3 Heterostructure as a High-Performance Hydrogen Evolution Reaction Catalyst in Both Alkaline and Acidic Solutions

Abstract: Exploring an efficient and pollution-free hydrogen evolution reaction (HER) electrocatalyst based on the combination of rare-earth metal and nonnoble metal is of significant importance. However, successfully achieving such a goal remains highly challenging. Herein, a nanosheet comprising a MoO2–CeF3 heterojunction (MoO2–CeF3/NF) is successfully prepared via a three-step method. (1) Growth of hexahedral nickel hydroxide [Ni­(OH)2] on a 3D nickel foam (NF) as the scaffold. (2) In situ hydrothermal growth of a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 50 publications
3
20
0
Order By: Relevance
“…[18] It is clearly shown that the mixedvalence of Ce 3+ and Ce 4+ exist in CeF 3 /α-FeOOH-400 nanohybrid. The peak of 684.4 eV is attributed to F1s (Figure 3d) [19] All above demonstrate the successful synthesis of CeF 3 /α-FeOOH.…”
Section: Introductionmentioning
confidence: 57%
“…[18] It is clearly shown that the mixedvalence of Ce 3+ and Ce 4+ exist in CeF 3 /α-FeOOH-400 nanohybrid. The peak of 684.4 eV is attributed to F1s (Figure 3d) [19] All above demonstrate the successful synthesis of CeF 3 /α-FeOOH.…”
Section: Introductionmentioning
confidence: 57%
“…To further demonstrate the increased intrinsic activity of HER, electrochemical impedance spectroscopy tests were performed. The Nyquist plots of these electrode materials and the corresponding results of the equivalent circuit fitting through the dual constant phase element (CPE) model are given in Figure c and Table S1. , In the dual CPE model, solution resistance ( R s ) is the resistance between the working electrode and the reference electrode, R1 and CPE1 are potential-independent and related to surface porosity, while resistance of charge transfer ( R ct ) and CPE2 are potential-dependent and related to HER. The R ct values of MoO 2 /Ni@NF and Ni@NF were 1.687 and 3.302 Ω, respectively, reflecting that MoO 2 /Ni@NF can exhibit better electron transport in HER …”
Section: Results and Discussionmentioning
confidence: 99%
“…Furthermore, to provide an in-depth insight into the intrinsic electrochemical activity of the catalysts, double layer capacitances (C dl ) of these electrocatalysts were calculated based on the CV curves (Figure S5) recorded in a relatively narrow potential window of 0.3-0.7 V (vs. RHE). [29] The electrochemical active surface area (ECSA) could then be estimated from C dl (Figure 3c). Based on the calculation, C dl of FeP/IF was 27.7 mF cm À 2 , which is greater than that of p-FeP/IF (22.7 mF cm À 2 ) and IF (3.1 mF cm À 2 ).…”
Section: Resultsmentioning
confidence: 99%